Non-uniform global methane distribution in Titan's troposphere evidenced by Cassini radio occultations - Tokano, Tetsuya (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2014)
The global distribution of atmospheric pressure retrieved from Cassini radio occultations is reanalyzed and interpreted in a meteorological context. The retrieval of Titan's atmospheric pressure profile from radio occultations is ambiguous because it depends on the methane mole fraction, which is not precisely known in the troposphere beyond the entry site of the Huygens Probe. The surface pressure at the geoid level in late northern winter decreases from south pole to north pole by similar to 15 hPa (1% of the surface pressure) if the data are retrieved under the assumption of a globally uniform methane distribution. However, this surface pressure distribution is inconsistent with the timing and location of observed convective clouds, surface wind direction and general circulation model prediction. A more realistic pressure distribution with a slight increase from the summer hemisphere to the winter hemisphere can be obtained if one assumes a substantially higher methane abundance in the southern (summer) hemisphere than in the northern (winter) hemisphere in the previous season. (c) 2013 Elsevier Inc. All rights reserved.